Where is the greatest risk of COVID-19 infection?: findings from Germany’s largest public health department, Cologne - Broichhaus, Lukas; Book, Julian; Feddern, Sven; Grüne, Barbara; Neuhann, Florian; Nießen, Johannes; Wiesmüller, Gerhard A.; Kossow, Annelene; Joisten, Christine (PLOS ONE, 2022)
SARS-CoV-2 has been spreading worldwide since late 2019. Before vaccines became available, exclusively non-pharmaceutical measures were used to prevent transmission of infection. Despite the fact that vaccinations are now available, it is still important to identify relevant transmission routes in order to contain the COVID-19- or further pandemics. Therefore, this study aims to systematically analyse data from the largest public health department in Germany to determine the significance of the various known and unknown transmission situations in terms of the proportion of infections.